Students’ understanding of question-level difficulty in thematic unit a textbooks in secondary education - Pedro Correia; Kristiani Kristiani; Paulo Alves Cabral; Julia Baquita Fatima Soares (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to examine students’ understanding in solving questions presented in the additional questions section of the Grade 11 chemistry textbook, as well as to identify the distribution of questioning levels contained in that section. The research was conducted at a general secondary school, involving 52 Grade 11 science-track (TC) students as the research participants. Data were collected using multiple techniques and instruments, including documentation, observation, questionnaires, and interviews. The findings indicate that the cognitive questions in the additional questions section are predominantly categorized at the processing level, accounting for 53%. Based on the questionnaire analysis, students’ level of understanding of input-level questions is classified as high (61%), while their understanding of processing-level questions falls within the sufficient category (48%), and output-level questions are also categorized as sufficient (49%). Furthermore, from the 15 questions administered to the students, 5.8% of students demonstrated a lack of understanding in answering the questions, 76.9% provided neutral responses, and 17.3% showed adequate understanding in their answers. Overall, the results suggest that students’ level of understanding can be classified as sufficient. Interview findings further reveal that several factors contribute to this condition, including students’ tendency to forget the subject content, lack of note-taking, and limited concentration during learning. Therefore, it is recommended that teachers provide additional questions as part of daily exercises or homework to enhance students’ understanding and learning outcomes.